High-Pump-Power Effects on the Four-Wave Mixing Signal for a Two-Level System Coupled With a Thermal Bath - Paz, José Luis; Récamier, José (Ciencia)
We present a formalism to incorporate high order effects of the pump field on the fourwave mixing signal for a two-level system immersed in a thermal bath. We derive analytical expressions for the nonlinear polarization in terms of the field amplitude and thermal noise parameters